Plan de negocios para la producción y comercialización de tarjetas en papel reciclable para la empresa G.L. ubicada en la ciudad de Zarzal – Valle del Cauca (2011)
With the aim of strengthening the entrepreneurial spirit that every person must possess A project was carried out to identify the feasibility of creating a company of production and commercialization of cards elaborated in paper recycled in the municipality of Zarzal Valley, denominated Cards G.L.